2016
DOI: 10.1021/acs.est.6b02067
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of Oxygen and Hydrogen Peroxide by Copper(II) Coupled with Hydroxylamine for Oxidation of Organic Contaminants

Abstract: This study reports that the combination of Cu(II) with hydroxylamine (HA) (referred to herein as Cu(II)/HA system) in situ generates H2O2 by reducing dissolved oxygen, subsequently producing reactive oxidants through the reaction of Cu(I) with H2O2. The external supply of H2O2 to the Cu(II)/HA system (i.e., the Cu(II)/H2O2/HA system) was found to further enhance the production of reactive oxidants. Both the Cu(II)/HA and Cu(II)/H2O2/HA systems effectively oxidized benzoate (BA) at pH between 4 and 8, yielding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(89 citation statements)
references
References 45 publications
0
88
1
Order By: Relevance
“…This suggested the generation of new chains from H 2 O 2 produced by GOx, continued even in a closed vial. The formed H 2 O 2 could further have reacted with Cu I species through a Fenton‐like reaction, yielding initiating radicals and new polymer chains (Scheme S2). To prevent formation of new chains, the reactive oxygen species should be eliminated and converted to inert products that do not interfere with propagating radicals or catalyst…”
Section: Figurementioning
confidence: 99%
“…This suggested the generation of new chains from H 2 O 2 produced by GOx, continued even in a closed vial. The formed H 2 O 2 could further have reacted with Cu I species through a Fenton‐like reaction, yielding initiating radicals and new polymer chains (Scheme S2). To prevent formation of new chains, the reactive oxygen species should be eliminated and converted to inert products that do not interfere with propagating radicals or catalyst…”
Section: Figurementioning
confidence: 99%
“…ESR and UV-Vis spectra revealed that, compared with the pure ZIF-8 nanoparticles, the Cu(I)@ZIF-8 nanoparticles generated more reactive oxygen species, which contributed to their antibacterial properties (Fig. 2b, c) [26,27].…”
Section: Characterization Of Cu(i)@zif-8 Nanoparticles and Plga/ Cu(imentioning
confidence: 99%
“…(4) and (5)) [40]. In addition, H 2 O 2 can be also activated by the regenerated metal (i.e., Fe(II) or Cu(I)), which could be formed from the reaction of Fe(III) or Cu(II) with photoelectrons [41]. Thus, the separation efficiency of holes and photoelectrons is improved and more hydroxyl radicals are continuously regenerated to degrade RhB and 2-CP.…”
Section: Oxidation Of 2-chlorophenolmentioning
confidence: 99%
“…Among them, the catalytic process of Cu-BiOBr is most complexed (Fig. 13C): first, the photoelectrons, which are formed on Cu-BiOBr in the presence of visible light, are captured by H 2 O 2 to generate hydroxyl radical that can more likely oxide Cu(II) to Cu(III) [40]; secondly, H 2 O 2 can react with Cu(I) to produce Cu(III), or Cu(II) is reduced by H 2 O 2 to superoxide radicals [41]; thirdly, the reaction of Cu(III) with organic contaminants generate Cu(II) and products. In the Vis/Cu-BiOBr/H 2 O 2 system, the formation of Cu(III) appears instead of hydroxyl radicals, which should be attributed to the chemical environment near the Cu atom [54].…”
Section: Possible Mechanismmentioning
confidence: 99%